Consequences of defaunation for a tropical tree community - Rhett D Harrison; Sylvester Tan; Joshua B. Plotkin; Ferry Slik; Matteo Detto; Tania Brenes; Akira Itoh; Stuart J. Davies (Ecology Letters, 2013)
Hunting affects a considerably greater area of the tropical forest biome than deforestation and logging combined. Often even large remote protected areas are depleted of a substantial proportion of their vertebrate fauna. However, understanding of the long‐term ecological consequences of defaunation in tropical forests remains poor. Using tree census data from a large‐scale plot monitored over a 15‐year period since the approximate onset of intense hunting, we provide a comprehensive assessment of the immediate consequences of defaunation for a tropical tree community. Our data strongly suggest that over‐hunting has engendered pervasive changes in tree population spatial structure and dynamics, leading to a consistent decline in local tree diversity over time. However, we do not find any support for suggestions that over‐hunting reduces above‐ground biomass or biomass accumulation rate in this forest. To maintain critical ecosystem processes in tropical forests increased efforts are required to protect and restore wildlife populations.